2018
DOI: 10.1016/j.ajog.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent fertility, pregnancy, and gynecologic outcomes after fetoscopic laser therapy for twin-twin transfusion syndrome compared with normal monochorionic twin gestations

Abstract: No adverse medium-term maternal effects with respect to fertility, obstetric, and gynecological outcomes were observed after fetoscopic laser therapy. However, these women reported more psychological or emotional problems than women with monochorionic diamniotic who did not have laser therapy, in particular when this was complicated by a fetal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Three out of 24 mothers who opted for MFS were diagnosed with mental health issues after birth of their baby, which they relate to events they experienced during their pregnancy trajectory. Earlier studies have reported depression and anxiety in patients undergoing fetal diagnosis or receiving fetal therapy, suggesting that women underdoing MFS require appropriate follow‐up and support to detect increased risks of mood and anxiety disorders 37‐39 . This was already the case in women with fetal SB in the pre‐fetal surgery era, 40,41 to which the stress of the MFS and potential complications of prematurity is now added.…”
Section: Discussionmentioning
confidence: 99%
“…Three out of 24 mothers who opted for MFS were diagnosed with mental health issues after birth of their baby, which they relate to events they experienced during their pregnancy trajectory. Earlier studies have reported depression and anxiety in patients undergoing fetal diagnosis or receiving fetal therapy, suggesting that women underdoing MFS require appropriate follow‐up and support to detect increased risks of mood and anxiety disorders 37‐39 . This was already the case in women with fetal SB in the pre‐fetal surgery era, 40,41 to which the stress of the MFS and potential complications of prematurity is now added.…”
Section: Discussionmentioning
confidence: 99%
“…Monochorionic diamniotic (MCDA) twins comprise 20-30% of spontaneous and 4-5% of iatrogenic twin gestations. MCDA pregnancies are at higher risk for perinatal complications than dichorionic twins and singleton pregnancies [23]. This is attributed to the presence of vascular anastomoses connecting the fetal circulations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that women with TTTS pregnancies may experience anxiety, depression, posttraumatic stress, and higher parenting pressure, thereby necessitating urgent clinical attention for their mental state. [6][7][8][9] However, based on current research, the lived experiences and actual thoughts during pregnancy and postpartum cannot be de nitively determined, which precludes adequate the provision of targeted treatments. In this regard, qualitative research is a method used to describe the life experiences of research subjects, capturing their emotions, beliefs, and behaviours.…”
Section: Introductionmentioning
confidence: 99%